THE EFFECT OF NATURAL HARMONY, SELF-RENEWAL, COMMUNITY, AND HEDONISM ON THE SATISFACTION OF RAFTING ADVENTURE TOURISM PRODUCT CONSUMERS - Setiawan, Zunan; Purwoko, Purwoko; Fikri, Muhammad Ali; Sulistyo, Beni Agus (Manajemen Bisnis, 2019)
This research examines the relationship of factors influencing consumer satisfaction namely natural harmony, self-renewal, community, and hedonism towards adventure tourism products. The research used multiple regression analysis to test the factors that influence consumer satisfaction on adventure tourism products. The respondents were 412 people who had taken adventure tours in groups in Yogyakarta and West Java last year. The characteristics of the participants were dominated by men with the age range of 18-50 years, and the occupational background were students and employees. The result of this research revealed that natural harmony, self-renewal, community, and hedonism were positive factors that had a significant influence on customer satisfaction toward rafting adventure tourism products. The research suggestions and implications are also discussed in this research.